Debates in physical education - Capel, Susan Anne, 1953-; Whitehead, Margaret, 1940- (Abingdon, Oxon ; New York : Routledge, 2020)
This new and updated second edition of Debates in Physical Education explores issues physical education teachers encounter in their daily lives. By engaging with both established and contemporary debates, this volume challenges readers to think about and reflect on the relative validity of positions presented in order to develop their own reasoned and personal view in relation to the topics explored. Divided into four accessible sections, this book investigates and offers fresh insight into topics of central importance in physical education. Chapters include, for example: Physical education as a means or as an end in itself; Knowledge for physical education; The physical education curriculum; Assessment in physical education; Technology, pedagogy and physical education. Physical education beyond schools and teachers. Designed to stimulate discussion and support readers in their own research, writing and practice, Debates in Physical Education will be a valuable resource for any student or practising teacher engaged in initial teacher education, continuing professional development or Master's level study.
Previous edition: 2013.
OCLC-licensed vendor bibliographic record.
Keywords: Physical education and training -- Study and teaching; Physical education and training -- Curricula; EDUCATION / Elementary; EDUCATION / Physical Education; EDUCATION / Secondary